A Case of Giant Extracalvarial Epidermal Cyst with Intracranial Extension - Vishal Bhasme; Divya Jain (Indian Journal of Neurosurgery)
Extracalvarial epidermal cysts are benign, uncommon type of tumors. Their incidence is around 0.2 to 1%. They are usually asymptomatic except for the absurd swelling over the scalp, which is associated with headache and rarely neurological deficits. Proper radiological diagnosis with accurate surgical approach and excision with capsule gives a good prognosis and prevents recurrence. Here we present the case of a 75-year-old gentleman with a large swelling over the scalp with mild pain. Surgical excision of the tumor with capsule was done followed by cranioplasty. The histopathology was consistent with an epidermal cyst. Case reports pertaining to such conditions are few.